Thermal diffusivity measurements of vapour grown carbon fibre composites, using the optical beam deflection technique - Macedo, F. J. (1999)
Carbon fibres are used widely as reinforcements for polymeric matrices in high-tech applications by virtue of their good mechanical, electrical and thermal properties. Vapour grown carbon fibres (VGCF) are a new type of fibres whose technological applications, namely reinforcements for thermoplastic matrix composites, are yet to be developed. Due to their potentially low cost and high production rates, VGCFs show promising new possibilities in this area. Recently, in industry worldwide, the potential of VGCFs in thermal and electrical applications such as solid-state batteries and electrostatic painting of high volume automotive plastic parts is increasingly being recognised. As a result, easy and non-destructive measurement of thermal and electrical properties of VGCF-based composites has become an important issue for use in industrial applications. In this study the optical beam deflection technique was used for the evaluation of the thermal diffusivity of vapour grown carbon fibres (VGCF) - polymer composites. It is shown that, for low diffusivities, simple approaches such as the “phase method'' or the ``zero crossing method'' are not valid and a multiparameter fitting to the amplitude values has to be used instead. The thermal diffusivity of the composites, measured along the direction of the fibre preferential orientation, increases with fibre content. This increase is not very marked, possibly due to poor adhesion between fibre and matrix.